Analisis Yuridis Otonomi Daerah Berbasis Kapasitas Lokal Studi Tentang Pengelolaan Keuangan Dan Aset Daerah Kabupaten Puncak Jaya) - SUWIGNYO, suwignyo, Dr. Aidul Fitriciada Azhari, SH., M.Hum, Dr. Nur Hadiantomo (2015)
The title of study is an analysis of regional autonomy based local juridical capacity, Study of Financial Management Model and the Regional Asset Distric of Puncak Jaya. This research background is Puncak Jaya Papua's special autonomy, get a 80% allocation of special autonomy funds. Puncak Jaya also has abundant natural resources, but a delay in development. The main factor is the system development is not based on local capacity. A legal perspective on local capacity refers to friedman's theory about the three systems of low, namely the legal aspects of saubstance, legal structure and legal culture. This research comprehensively look at the three parts are within the scope of Puncak Jaya. This research uses empirisn jurodical technic approach of qualitative analysis, the data source is the legislation on local governent, local finance and regional autonomy, regional executive report from authorized agencis, interviews with government authorities and finance at the Distric Puncak Jaya. Through this method to obtain maximum results ang accountability. Low No. 23 Year 2014 Article 279 - Article 280 describes local capacity in regional development. Authorities interpretet as the authority and capacity to report and financial pengelolaan Puncak Jaya Distric. But the results showed thad the Puncak Jaya has not maximum capacity strengthening awareness-forming to deliver an advanced capacity for the region's autonomy and well-being.